Obligasi Dan Sukuk Dalam Perspektif Keuangan Islam (Suatu Kajian Perbandingan) - Muhammad Kamal Zubair (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
This article study about sukuk is known as sharia bonds with compare to obligation as the investment instrument in capital market. Sukuk investment is often regard as identical with obligation. There are number of basic differences between the two instrument, that is the use of sukuk instruments in investment the profit of which is divided with profit sharing, sukuk needs to have an underlying transaction in the form of tangible assets and sukuk use religious advice that govern syariah bond.